The chemical structure of a 30 cm methanol pool fire. (25th April 2020) - Falkenstein‐Smith, Ryan; Sung, Kunhyuk; Chen, Jian; Hamins, Anthony
Summary: This study documents a series of time‐averaged gas species measurements made along the centerline of a 30 cm methanol pool fire steadily burning in a quiescent environment. All gas species measurements were obtained using a gas chromatograph/mass spectrometer system (GC/MS). Measurements were made at different heights along the centerline of the fire and repeated at least twice for each location. Gas species volume fractions were determined via the GC/MS using predetermined calibration factors. The gas species volume fractions were compared at different heights within the methanol fire.